2018
DOI: 10.1016/j.jpainsymman.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Opioid Therapy on Sleep and Respiratory Patterns in Adults With Advanced Cancer Receiving Palliative Care

Abstract: Context. In advanced cancer, abnormal sleep patterns may contribute to poor quality of life, but the impact of opioidrelated sleep disorders has not been explored in detail in these patients. Objective. To document sleep and respiratory patterns in patients with cancer, receiving a range of opioids, determine factors that contribute to severity of central or obstructive apnea, and to what extent these contribute to sleep disturbance. Methods. Adults with advanced cancer admitted to a palliative care service un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Our methodology was to exclude patients with great pain levels, patients with poor general health, and patients on specific treatment interacting with sleep quality. That allowed us to select a coherent cohort of patients to evaluate the quality of life and its correlation with sleep quality independently from the influence of pain or general health [5]. Questionnaires are a validated tool to assess global health or symptom severity [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our methodology was to exclude patients with great pain levels, patients with poor general health, and patients on specific treatment interacting with sleep quality. That allowed us to select a coherent cohort of patients to evaluate the quality of life and its correlation with sleep quality independently from the influence of pain or general health [5]. Questionnaires are a validated tool to assess global health or symptom severity [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is proposed in stage IV of the disease if there are no contraindications. Its impact on the general status, quality of life, and sleep quality is scarcely reported [4][5][6]. These interactions between burdensome therapeutic protocols and quality of life or sleep were reported in other cancer types [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 146 , 148 Significant sleep disturbances were also demonstrated in an observational investigation in patients with advanced cancer (84%). 147 Sleep apnea may contribute to arrhythmias, myocardial infarction, stroke and increased mortality. 17 , 26 , 146 , 150–152 …”
Section: Resultsmentioning
confidence: 99%
“…Opioid use may induce sleep-disordered breathing (SDB), mostly of the central type, because of the influence of opioids on breathing rhythm and control of ventilation. 17,18,[146][147][148][149] Opioids can also trigger or exacerbate obstructive sleep apnea in predisposed individuals by causing relaxation of pharyngeal tone and increasing the collapsibility of the airways. 17,146,147 Studies included in two systematic reviews demonstrated high prevalence of SDB and central sleep apnea (CSA) in patients using opioids for chronic pain, ranging from 75% to 91%, and 18% to 33%, respectively.…”
Section: Influence On Sleep Quality and Sleep-disordered Breathingmentioning
confidence: 99%
See 1 more Smart Citation